Comparison of quality and microbial community of Doubanjiang by traditional fermentation and industrial fermentation - WANG Pengyue, DENG Weiqin, WANG Fang, WANG Xinlu, LI Long, WANG Zeliang (Zhongguo niangzao)
In order to investigate the effects of different production processes on the quality of commercial Doubanjiang, using the traditionally fermented Doubanjiang (TFD) and industrially fermented Doubanjiang (IFD) with consistent production cycles as research objects, the microbial community composition of them was analyzed using Illumina NovaSeq sequencing technology. The contents of free amino acid, volatile flavor substances and biogenic amine were detected by HPLC and GC-MS. The results showed that amino acid composition of two kinds of Doubanjiang was identical, but the content of 16 kinds of free amino acids were significantly different (P<0.05), and the proportion of fresh and sweet amino acid in TFD was higher. There were significant differences in the volatile flavor substances, and ethyl 3-methylbutyrate, ethyl 4-methyl-valerate, linalsol and β-ionone were the distinguishing differential aroma components in the two kinds of Doubanjiang. There were some differences in the dominant communities of the two kinds of Doubanjiang. The dominant communities (relative abundance>0.5%) in TFD were 16 bacterial genera including Virgibacillus and Lentibacillus, and 4 fungi genera including Starmerella and Wickerhamiella. The dominant communities in IFD were 7 bacterial genera, including Bacillus and Staphylococcus, and 5 fungal genera, including Aspergillus and Starmerella. The total biogenic amine content of TFD (299.85 mg/kg) was higher than that of IFD (272.37 mg/kg), and the contents of histamine, β-phenylethylamine and spermine were significantly different between them. Overall, IFD was better in terms of flavor and safety.